[tex]x= \sqrt{2}x+3 /- \sqrt{2}x \\ x- \sqrt{2}x=3 \\ x(1- \sqrt{2} )=3 /:(1- \sqrt{2} ) \\ x= \frac{3}{1- \sqrt{2} }
\\ [/tex]
Rationalizăm, amplificând fracția cu [tex](1+ \sqrt{2} )[/tex]
[tex]x= \frac{3(1+ \sqrt{2} )}{(1- \sqrt{2} )(1+ \sqrt{2} )} \\ x= \frac{3(1+ \sqrt{2} )}{ 1^{2} -( \sqrt{2}^{2} )} \\ x= \frac{3(1+ \sqrt{2} )}{1-2} \\ x= \frac{3(1+ \sqrt{2} )}{-1} \\ x=-3(1+ \sqrt{2} )[/tex]
Observ că nu se vede ok prima parte.
[tex]x= \sqrt{2}x+3 / - \sqrt{2}x \\ x- \sqrt{2}x=3 \\ x(1- \sqrt{2} )=3 /:(1- \sqrt{2} ) \\ x= \frac{3}{1- \sqrt{2} } [/tex]